Helional induces Ca2+ decrease and serotonin secretion of QGP-1 cells via a PKG-mediated pathway. (October 2016) - Kalbe, Benjamin; Schlimm, Marian; Mohrhardt, Julia; Scholz, Paul; Jansen, Fabian; Hatt, Hanns; Osterloh, Sabrina
Abstract : The secretion, motility and transport by intestinal tissues are regulated among others by specialized neuroendocrine cells, the so-called enterochromaffin (EC) cells. These cells detect different luminal stimuli, such as mechanical stimuli, fatty acids, glucose and distinct chemosensory substances. The EC cells react to the changes in their environment through the release of transmitter molecules, most importantly serotonin, to mediate the corresponding physiological response. However, little is known about the molecular targets of the chemical stimuli delivered from consumed food, spices and cosmetics within EC cells. In this study, we evaluated the expression of the olfactory receptor (OR) 2J3 in the human pancreatic EC cell line QGP-1 at the mRNA and protein levels. Using ratiofluorometric Ca 2+ imaging experiments, we demonstrated that the OR2J3-specific agonist helional induces a transient dose-dependent decrease in the intracellular Ca 2+ levels. This Ca 2+ decrease is mediated by protein kinase G (PKG) on the basis that the specific pharmacological inhibition of PKG with Rp-8-pCPT-cGMPS abolished the helional-induced Ca 2+ response. Furthermore, stimulation of QGP-1 cells with helional caused a dose-dependent release of serotonin that was comparable with the release induced by the application of a direct PKG activator (8-bromo-cGMP). Taken together, our results demonstrate that luminal odorants can be detected by specific ORs in QGP-1 cells and thus cause the directed release of serotonin and a PKG-dependent decrease in intracellular Ca 2+ .